Associations Between the Knowledge of Different Food Categories and Glycemia in Chinese Adult Patients With Type 2 Diabetes. (June 2020) - Xue, Yuan; Zhang, Xiao-Yan; Zhou, Hui-Juan; Ojo, Omorogieva; Wang, Qi; Wang, Li-Li; Jiang, Qing; Liu, Ting; Wang, Xiao-Hua
This study aims to evaluate the levels of knowledge of different food categories and analyze the association between the levels of dietary knowledge and glycemia in Chinese adult patients with type 2 diabetes mellitus (T2DM). A cross-sectional study design was adopted. A total of 334 patients with T2DM were recruited from six hospitals from July to October 2014 in China. The Diabetes Dietary Knowledge Scale was utilized to obtain dietary knowledge. The results showed the item examining knowledge of carbohydrates received the highest score, whereas the item examining knowledge of healthy fats received the lowest score. The item "nuts" ( B = −0.49; 95% confidence interval [CI] = [0.38, 0.99]) was associated with the incidence of hyperglycemia. The item "foods when hypoglycemic" ( B = 0.42; 95% CI = [1.22, 2.07]) was associated with the incidence of hypoglycemia. There were different knowledge levels of different food categories in patients with T2DM, and these have implications for blood glucose control.